A collaborative work on quantitative HPLC methods for the routine determination of atranol and chloroatranol in moss extracts. (4th November 2018) - Goursot, Jean‐François; ,
Abstract: Moss extracts have been found to initiate skin sensitization. For this reason, oakmoss extracts are part of the diagnostic screening test for fragrance contact allergy. Atranol and chloroatranol are suspected to be responsible for the sensitizing properties of these extracts, and their content has consequently been limited to 100 ppm in moss extracts by the International Fragrance Association (IFRA). In this context, using round‐robin tests, PRODAROM (the French national association of fragrance manufacturers) has developed different analytical methods for the routine quantification of these two suspected skin allergens in moss extracts that are easily applicable in quality control laboratories. Reversed‐phase high‐performance liquid chromatography (HPLC) with diode‐array detection (DAD) and external calibration allowed the quantification of both analytes in solution in the 10–100 mg L −1 range. In order to enhance the specificity of the method, mass spectrometry (MS) in single ion monitoring (SIM) mode was also used. To solve matrix‐effect problems, the use of in‐matrix calibration solutions, or the extrapolative dilution approach (EDA) using solvent calibration were mandatory. The liquid chromatography–mass spectrometry (LC‐MS) method was validated in the 1–10 mg L −1 range for both allergens in solution. Abstract : Development of two HPLC methods, with UV or MS detection, for the quantification of two allergens in moss extracts. Performance of both methods was investigated through round robin tests within the scientific and technical committee of Prodarom.